2019
DOI: 10.4081/cp.2019.1129
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Pregnancy with Suspicion of Superfetation after the Intrauterine Insemination Cycle with Ovulation Induction Using Clomiphene Citrate: A Case Report

Abstract: At 22 days after intrauterine insemination with ovulation induction using clomiphene citrate at a previous hospital, a 30-year-old woman was admitted to our hospital owing to right lower quadrant abdominal pain. We diagnosed threatened abortion because of a gestational sac in the uterus on transvaginal ultrasonography. The next day, she complained of increased abdominal pain. Transvaginal ultrasonography revealed a gestational sac-like structure in the echo free space. She was diagnosed with heterotopic pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…While the incidence of heterotopic pregnancy is estimated to be 1 in 30,000 spontaneous pregnancies, the rate increases to as high as 1 in 100 pregnancies when ART is used. 4 Our review of the literature found that the strongest risk factor for developing a heterotopic pregnancy was ovarian hyperstimulation, which is commonly seen in females using ART. We suggest that heterotopic pregnancy should be considered in the differential diagnosis of abdominal pain for females who have undergone ovarian stimulation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…While the incidence of heterotopic pregnancy is estimated to be 1 in 30,000 spontaneous pregnancies, the rate increases to as high as 1 in 100 pregnancies when ART is used. 4 Our review of the literature found that the strongest risk factor for developing a heterotopic pregnancy was ovarian hyperstimulation, which is commonly seen in females using ART. We suggest that heterotopic pregnancy should be considered in the differential diagnosis of abdominal pain for females who have undergone ovarian stimulation.…”
Section: Discussionmentioning
confidence: 93%
“…Human superfetation has been proposed previously, but evidence is considered circumstantial, and reports are extremely rare. 4 Nonviable pregnancies, such as those destined to miscarry and tubal ectopic pregnancies, also follow different growth trajectories than viable pregnancies. 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon arises when superfetation occurs intrauterine on top of an ectopic pregnancy or vice versa. 4,5,7,14,15 This coexistence of both intrauterine and extrauterine pregnancies is referred to as HP. 16 HP, a rare phenomenon in spontaneous pregnancies with an incidence of 1 in 30,000, has seen a noteworthy increase in occurrence due to the widespread use of ARTs.…”
Section: F I G U R Ementioning
confidence: 99%